A nickel-cobalt-manganese ternary precursor and preparation method thereof, a nickel-cobalt-manganese ternary material and a secondary battery

By preparing nickel-cobalt-manganese ternary precursors and controlling process parameters, the problems of few pores and uneven distribution of particles in existing lithium-ion battery materials are solved, and the high-rate performance and long life of lithium-ion batteries are achieved.

CN119735249APending Publication Date: 2025-04-01ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411965449.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The internal structure of the ternary polycrystalline precursor materials of existing lithium-ion batteries has few pores and uneven distribution, resulting in a single diffusion path, large diffusion resistance, poor rate performance, and unstable structural strength and easy cracking, resulting in a short battery life, a lower capacity, and a reduced safety performance.

Method used

A nickel-cobalt-manganese ternary precursor with a chemical formula of (NixCoyMnzMa)(OH)2 is used. By controlling process parameters such as the pH of the base liquid, ammonia value, reaction system pH, ammonia value and reaction atmosphere oxygen content, a core-shell structure high-nickel precursor with loose core porous and primary shell particles growing radially is prepared.

Benefits of technology

The lithium ion diffusion channel of nickel-cobalt-manganese ternary material is improved, the contact surface between the positive electrode material and the electrolyte is increased, the reactive site is improved, and the first charge and discharge performance, cycle performance and rate performance of the battery is significantly improved, which extends the battery life and improves safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735249A_ABST
    Figure CN119735249A_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of battery active materials, and specifically discloses a nickel-cobalt-manganese ternary precursor and a preparation method thereof, a nickel-cobalt-manganese ternary material and a secondary battery. The chemical formula of the nickel-cobalt-manganese ternary precursor is (Ni x Co y Mn z M a )(OH)2, 0.9<x≤0.98, y>0, z>0, x+y+z=1, 0≤a≤0.01, M is a doping element; the secondary particles are composed of primary particles, including a core and a shell; the tap density of the secondary particles is 2.0g / cm 3 <TD<2.2g / cm 3 , the specific surface area BET is 10m 2 / g<BET<20m 2 / g. The nickel-cobalt-manganese ternary precursor is a core-shell structured high-nickel precursor with a loose and porous core and radially growing primary particles in the outer shell, and has the advantages of high tap density and specific surface area. The use of the precursor to prepare nickel-cobalt-manganese ternary materials and use it as a positive electrode material can significantly improve battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery active materials, and in particular to a nickel-cobalt-manganese ternary precursor and a preparation method thereof, a nickel-cobalt-manganese ternary material and a secondary battery. Background Art

[0002] As a new type of high-energy green battery, lithium-ion battery has the characteristics of high energy density, long cycle life, wide application range and no memory effect compared with traditional energy batteries. In addition, in recent years, stimulated by the demand of new energy market, the development of lithium-ion power batteries has been continuously promoted. The performance of positive electrode materials is the key to determine the performance of lithium-ion batteries. Nickel-cobalt-manganese ternary positive electrode materials have become ideal electric vehicle battery materials because of their high theoretical energy density and long cycle life.

[0003] With the continuous expansion and extension of lithium-ion battery application scenarios, the energy density and rate performance requirements of lithium-ion batteries are getting higher and higher to meet the use requirements of different equipment and application environments. However, the internal structure of the particles of the common lithium-ion battery ternary polycrystalline precursor materials is generally a structure with few pores and uneven internal distribution. The use of them to prepare positive electrode materials and then use them in batteries will result in a single lithium ion diffusion path, large diffusion resistance, and poor rate performance; and with continuous charging and discharging, the particle structure strength is unstable and cracks are easily generated in the particle unit, which reacts with the electrolyte to shorten the battery life, reduce the capacity, and reduce safety performance during use. Summary of the invention

[0004] In view of the shortcomings of the prior art described above, the object of the present invention is to provide a nickel-cobalt-manganese ternary precursor and a preparation method thereof, a nickel-cobalt-manganese ternary material and a secondary battery, which are used to solve the problems in the prior art that the precursor material particles have few internal pores and are unevenly distributed, the particle structure strength is unstable, and it is easy to crack, thereby causing poor battery performance and reduced safety.

[0005] In order to achieve the above-mentioned object and other related objects, the present invention provides a nickel-cobalt-manganese ternary precursor, wherein the chemical formula of the nickel-cobalt-manganese ternary precursor is (Ni x Co y Mn z M a )(OH)2, wherein 0.9<x≤0.98, y>0, z>0, x+y+z=1, 0≤a≤0.01, M is a doping element;

[0006] The nickel-cobalt-manganese ternary precursor is a secondary particle composed of primary particles, including a core and a shell;

[0007] The tap density TD of the secondary particles is 2.0 g / cm 3<TD<2.2g / cm 3 , the specific surface area BET is 10m 2 / g<BET<20m 2 / g.

[0008] Furthermore, the inner core has pores, and the porosity is 5% to 10%.

[0009] Furthermore, the shell has pores, and the porosity is 1% to 5%.

[0010] Furthermore, the shell is composed of primary particles, and the primary particles growing radially toward the center of the shell account for more than 80%.

[0011] Furthermore, more than 90% of the primary particles in the shell have an aspect ratio of 5.0 to 15.0.

[0012] Furthermore, M is selected from at least one of Al, Mg, Zr, Ti, Cu and Zn.

[0013] Furthermore, the mass content of M is 3000 ppm to 8000 ppm.

[0014] Furthermore, the particle size distribution width Span of the secondary particles is 0.32 to 0.45.

[0015] Furthermore, in the X-ray diffraction pattern of the nickel-cobalt-manganese ternary precursor, the peak intensity ratio of the (001) peak to the (101) peak is (001) / I (101) It is 1.0~1.5.

[0016] Furthermore, the secondary particle structure is spherical or quasi-spherical, and 90%<Q<100%, where Q is the roundness.

[0017] Furthermore, the secondary particle size D50 is 9.0 μm to 15.0 μm.

[0018] Furthermore, the distance from the center of the inner core to the outer wall of the inner core is 5 to 9 μm.

[0019] Furthermore, the shell has a thickness of 4 μm to 6 μm.

[0020] Furthermore, the longitudinal cross-sectional area of ​​the shell accounts for 30% to 50% of the longitudinal cross-sectional area of ​​the secondary particle.

[0021] Furthermore, the primary particles are spindle-shaped.

[0022] Furthermore, the length of the primary particles is 200 nm to 700 nm.

[0023] Furthermore, the width of the primary particles is 40 nm to 90 nm.

[0024] Furthermore, the angle between the length direction of the primary particle and the centripetal force direction is less than or equal to 30°.

[0025] The present invention also provides a method for preparing the nickel-cobalt-manganese ternary precursor as described above, comprising the following steps:

[0026] S1. Prepare a base solution, wherein the pH of the base solution is 11 to 13 and the base solution contains 5 g / L to 8 g / L of a complexing agent;

[0027] S2, adding liquid A, liquid B and liquid C to the base liquid at the same time to prepare seed crystals;

[0028] S3, adding liquid A, liquid B and liquid C to the seed crystal at the same time, controlling the pH of the reaction system to 10-12, the concentration of the complexing agent in the reaction system to 3 g / L-6 g / L, and preparing the nickel-cobalt-manganese ternary precursor under a second oxidizing atmosphere;

[0029] The A solution includes a nickel source, a cobalt source and a manganese source, the B solution includes a precipitant, and the C solution includes a complexing agent;

[0030] The volume ratio of oxygen to protective gas in the second oxidizing atmosphere is 1:0.2-10, and the oxygen content in the second oxidizing atmosphere gradually decreases as the particle size increases until particles meeting the target particle size requirements are obtained. Further, the oxygen content in the second oxidizing atmosphere gradually decreases as the particle size increases until particles meeting the target particle size requirements are obtained, including:

[0031] When the seed crystal grows to a particle size that reaches a first preset particle size requirement, the volume ratio of oxygen to protective gas in the second oxidizing atmosphere is 1:0.5-5.0;

[0032] When the particle size reaches the second preset particle size requirement, the volume ratio of oxygen to protective gas in the second oxidizing atmosphere is 1:2-10;

[0033] The first preset particle size requirement is smaller than the second preset particle size requirement.

[0034] Furthermore, in the liquid A, the molar ratio of nickel ions, cobalt ions and manganese ions is 0.9-0.98:0.01-0.05:0.01-0.05.

[0035] Furthermore, the A liquid also includes a salt containing a doping element M. Optionally, the M element is selected from at least one of Al, Mg, Zr, Ti, Cu or Zn.

[0036] Furthermore, the metal ion concentration in the liquid A is 1.5 mol / L to 2.5 mol / L.

[0037] Furthermore, the liquid B includes a precipitant with a mass concentration of 25wt% to 32wt%.

[0038] Furthermore, the C liquid includes a complexing agent with a mass concentration of 12wt% to 20wt%.

[0039] Furthermore, the base liquid is prepared under a protective gas atmosphere.

[0040] Furthermore, the base liquid is prepared at 40°C to 70°C.

[0041] Furthermore, when preparing the base liquid, the stirring speed is 400 rpm to 800 rpm.

[0042] Further, step S2 is performed under a first oxidizing atmosphere, and the flow ratio of oxygen to protective gas in the first oxidizing atmosphere is 1:0.2-5.0.

[0043] Furthermore, in step S2, the flow ratio of the A liquid, B liquid and C liquid added simultaneously to the base liquid is 100-200:20-50:1N4.

[0044] Furthermore, in step S2 and / or S3, the reaction temperature is 40°C to 70°C.

[0045] Furthermore, in step S2 and / or S3, the stirring speed is controlled at 300 rpm to 600 rpm.

[0046] Furthermore, in step S3, the flow ratio of the liquid A, liquid B and liquid C added simultaneously to the seed crystal is 100-200:20-40:1-4.

[0047] The present invention also provides a nickel-cobalt-manganese ternary material, which is prepared by mixing a precursor with a lithium source and then sintering. The precursor includes the nickel-cobalt-manganese ternary precursor as described above and / or the nickel-cobalt-manganese ternary precursor prepared according to the method as described above.

[0048] The present invention also provides a secondary battery, comprising a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises the nickel-cobalt-manganese ternary material as described above.

[0049] As described above, the nickel-cobalt-manganese ternary precursor and preparation method thereof, the nickel-cobalt-manganese ternary material and the secondary battery of the present invention have the following beneficial effects:

[0050] The present invention controls the porosity and distribution uniformity of the inner core and the outer shell of the nickel-cobalt-manganese ternary precursor by regulating key process parameters (such as the pH value of the base liquid, the ammonia value, the pH value of the reaction system, the oxygen content of the reaction atmosphere, etc.), and controls the particle size of the nickel-cobalt-manganese ternary precursor, as well as the growth direction, morphology and size of the outer shell primary particles, thereby preparing a core-shell structured high-nickel precursor with a loose and porous inner core and outer shell primary particles growing along the radial direction.

[0051] The nickel-cobalt-manganese ternary precursor provided by the present invention has high tap density and specific surface area, and the particle size distribution is uniform; the material is loose and porous, especially gaps will be generated between primary particles, forming a larger pore structure; the inner core pores are rich and evenly distributed, which can effectively increase the lithium ion diffusion channel of the subsequently prepared nickel-cobalt-manganese ternary material, and can also make the contact surface between the prepared positive electrode material and the electrolyte larger, with higher reaction active sites, which is beneficial to improving the capacity of the positive electrode material under high rate during charging and discharging; the outer shell primary particles grow radially, are spindle-shaped, and are arranged regularly, which can effectively alleviate the stress release of the positive electrode material during the charging and discharging process, and alleviate the material structure collapse caused by anisotropy, so that the positive electrode material has more excellent cycle stability under high rate charging and discharging.

[0052] In general, applying the nickel-cobalt-manganese ternary material prepared by the nickel-cobalt-manganese ternary precursor of the present invention as a positive electrode material to a secondary battery can significantly improve the battery's initial charge and discharge performance, cycle performance, and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is the XRD pattern of the nickel-cobalt-manganese ternary precursor prepared in Example 1.

[0054] Figure 2 This is the SEM image of the nickel-cobalt-manganese ternary precursor prepared in Example 1.

[0055] Figure 3 This is the SEM cross-sectional (CP) image of the nickel-cobalt-manganese ternary precursor prepared in Example 1. DETAILED DESCRIPTION

[0056] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0057] In the present invention, unless otherwise specified, the term "plurality" means two or more.

[0058] The character " / " indicates that the objects before and after are in an "or" relationship. For example, A / B means: A or B.

[0059] The term "and / or" is a description of the association relationship between objects, indicating that three relationships can exist. For example, A and / or B means: A or B, or, A and B.

[0060] One embodiment of the present invention provides a nickel-cobalt-manganese ternary precursor, wherein the chemical formula of the nickel-cobalt-manganese ternary precursor is (Ni x Co y Mn z M a )(OH)2, wherein 0.9<x≤0.98, y>0, z>0, x+y+z=1, 0≤a≤0.01, M is a doping element, including but not limited to Al, Mg, Zr, Ti, Cu, Zn, etc., and the mass content is, for example, 3000ppm~8000ppm;

[0061] The nickel-cobalt-manganese ternary precursor is a secondary particle composed of primary particles, including a core and a shell;

[0062] The tap density TD of the secondary particles is 2.0 g / cm 3 <TD<2.2g / cm 3 , the specific surface area BET is 10m 2 / g<BET<20m 2 / g.

[0063] The nickel-cobalt-manganese ternary precursor provided in the above embodiment of the present invention is a core-shell structure high-nickel precursor, and has both a high tap density and a high specific surface area. A higher tap density means that the material particles are arranged more densely inside, and the particle structure strength is more stable, which is beneficial to improving the capacity, stability and cycle life of the battery; a higher specific surface area indicates that its internal porosity is larger, which is beneficial to increasing the lithium ion diffusion channel of the subsequently prepared nickel-cobalt-manganese ternary material, and can also make the prepared positive electrode material have a larger contact area with the electrolyte, and have a higher reaction active site, which is beneficial to improving the capacity of the positive electrode material at high rates during charging and discharging, especially.

[0064] In some embodiments, the inner core has pores with a porosity of 5% to 10%. The inner core has abundant pores and is evenly distributed, which can effectively increase the lithium ion diffusion channel of the subsequently prepared nickel-cobalt-manganese ternary material, and can also make the prepared positive electrode material have a larger contact surface with the electrolyte, and have a higher reaction active site, which is beneficial to improving the capacity of the positive electrode material at high rates during charging and discharging, especially.

[0065] In some embodiments, the shell has pores, and the porosity is 1%N5%. Compared with the core, the porosity of the precursor shell is lower, which can provide favorable conditions for the full infiltration of the electrolyte during the charge and discharge process, thereby obtaining a higher specific capacity, and can ensure the stability of the particle structure strength and avoid easy cracking.

[0066] In some embodiments, the shell is composed of regularly arranged primary particles, and the primary particles in the shell that grow radially toward the center of the circle account for more than 80%. Most of the primary particles in the precursor shell grow radially, which can effectively alleviate the stress release of the positive electrode material during the charging and discharging process, and slow down the collapse of the material structure caused by anisotropy, so that the positive electrode material has better cycle stability under high-rate charging and discharging. Furthermore, in some embodiments, the angle between the length direction of the primary particle and the centripetal force direction is less than or equal to 30°.

[0067] In some embodiments, the primary particles in the shell are spindle-shaped, which is a slender shape with gradually narrowed ends, similar to a spindle or a rugby ball, with a thicker middle part and gradually thinner ends (see Figure 3 ), and more than 90% of the primary particles in the shell have an aspect ratio of 5.0 to 15.0, which can make the precursor better integrated with the lithium source during the sintering process. Further, in some embodiments, the length of the primary particles is 200nm to 700nm, and the width of the primary particles is 40nm to 90nm.

[0068] In some embodiments, the secondary particle size D50 is 9.0 μm to 15.0 μm, the particle size distribution width Span is 0.32 to 0.45, and the particle size distribution is uniform. Further, in some embodiments, the distance from the center of the core to the outer wall of the core (i.e., the core radius) is 5 to 9 μm, and the thickness of the shell is 4 to 6 μm. Furthermore, in some embodiments, the longitudinal cross-sectional area of ​​the shell accounts for 30% to 50% of the longitudinal cross-sectional area of ​​the secondary particle.

[0069] In some embodiments, in the X-ray diffraction pattern of the nickel-cobalt-manganese ternary precursor, the peak intensity ratio of the (001) peak to the (101) peak is (001) / I (101) The ratio of (001) crystal plane to that of (1.0-1.5) is reduced, the transmission distance of lithium ions is shortened, the embedding of lithium ions is facilitated, and the residual lithium on the surface of the positive electrode material is reduced, thereby effectively reducing the residual alkali on the surface of the positive electrode material and improving the capacity and cycle stability of the positive electrode material.

[0070] In some embodiments, the secondary particle structure is spherical or quasi-spherical, and 90%<Q<100%, where Q is the roundness.

[0071] Another embodiment of the present invention provides a method for preparing the nickel-cobalt-manganese ternary precursor as described above, comprising the following steps:

[0072] S1. Prepare a base solution, wherein the pH of the base solution is 11 to 13 and the base solution contains 5 g / L to 8 g / L of a complexing agent;

[0073] S2, adding liquid A, liquid B and liquid C to the base liquid at the same time to prepare seed crystals;

[0074] S3, adding liquid A, liquid B and liquid C to the seed crystal at the same time, controlling the pH of the reaction system to 10-12, the concentration of the complexing agent in the reaction system to 3 g / L-6 g / L, and preparing the nickel-cobalt-manganese ternary precursor under a second oxidizing atmosphere;

[0075] The A solution includes a nickel source, a cobalt source and a manganese source, the B solution includes a precipitant, and the C solution includes a complexing agent;

[0076] The volume ratio of oxygen to protective gas in the second oxidizing atmosphere is 1:0.2-10, and the oxygen content in the second oxidizing atmosphere gradually decreases as the particle size increases until particles meeting the target particle size requirements are obtained.

[0077] The present invention prepares a core-shell structured high-nickel precursor with a loose and porous inner core and outer shell primary particles growing along the radial direction by controlling reaction conditions (such as base liquid pH, ammonia value, reaction system pH, ammonia value, reaction atmosphere oxygen content, etc.).

[0078] The present invention specially sets the pH value and the ammonia value, the base liquid has a high pH value and a high ammonia value, and then reduces the pH value and the ammonia value in the seed crystal growth stage, that is, reduces the pH value and the concentration of the complexing agent in the reaction system, and gradually reduces the oxygen content in the seed crystal growth stage, so as to control the porosity and distribution uniformity of the inner core and the outer shell of the nickel-cobalt-manganese ternary precursor, and control the particle size of the nickel-cobalt-manganese ternary precursor, as well as the growth direction, morphology and size of the primary particles of the outer shell, and enhance the (101) peak in the precursor crystal structure XRD, and the peak intensity ratio of the (001) peak to the (101) peak is 1.0-1.5. The nickel-cobalt-manganese ternary material prepared from the precursor with such indicators has better electrical properties, and can significantly improve the initial charge and discharge performance, cycle performance and rate performance of the battery.

[0079] If the pH and high ammonia value of the base solution are low, the pH and ammonia value will be even lower in the later stage of seed crystal growth, which will cause the particles to grow too fast and easily agglomerate, resulting in a lower tap density of the finished material, poor sphericity, and uneven particle size distribution. (001) / I (101) becomes larger, and the (001) crystal plane accounts for too high a proportion, resulting in poor specific capacity of the positive electrode material.

[0080] If the seed growth stage is not carried out in an oxidizing atmosphere or the oxygen content of the oxidizing atmosphere is too high, the particles will grow too fast, resulting in a lower tap density of the finished material and uneven particle size distribution. (001) / I (101) It becomes larger, and the (001) crystal plane accounts for too high a proportion, resulting in poor performance of the positive electrode material's specific capacity, and also causing problems such as large gas production and poor cycle performance.

[0081] In some embodiments, the oxygen content in the second oxidizing atmosphere is gradually reduced as the particle size increases until particles meeting the target particle size requirements are obtained, comprising:

[0082] When the seed crystal grows to a particle size that reaches a first preset particle size requirement, the volume ratio of oxygen to protective gas in the second oxidizing atmosphere is 1:0.5-5.0;

[0083] When the particle size reaches the second preset particle size requirement, the volume ratio of oxygen to protective gas in the second oxidizing atmosphere is 1:2-10;

[0084] The first preset particle size requirement is smaller than the second preset particle size requirement. The first preset particle size requirement is, for example, 0.4 μm to 0.6 μm, and the second preset particle size is, for example, 0.7 μm to 0.8 μm.

[0085] In the present invention, the oxygen content is gradually reduced in the seed crystal growth stage, mainly according to the particle size, and the oxygen content is reduced in two steps, which can effectively control the particle growth and facilitate operation.

[0086] In some embodiments, in the liquid A, the molar ratio of nickel ions, cobalt ions and manganese ions is 0.9-0.98: 0.01-0.05: 0.01-0.05. Further, in some embodiments, the liquid A also includes a salt containing a doping element M, and in the liquid A, the molar ratio of nickel ions, cobalt ions, manganese ions and doping element M ions is 0.9-0.98: 0.01-0.05: 0.01-0.05: 0-0.008, so that the finished material contains the doping element M, and the doping element M includes but is not limited to Al, Mg, Zr, Ti, Cu, Zn, etc. The ratio of each raw material in the liquid A can be adjusted within the above range according to the content of each element in the target product.

[0087] In some embodiments, the metal ion concentration in the A solution is 1.5 mol / L to 2.5 mol / L; the B solution includes a precipitant with a mass concentration of 25 wt% to 32 wt%, and the C solution includes a complexing agent with a mass concentration of 12 wt% to 20 wt%.

[0088] In some embodiments, the nickel source is selected from a soluble nickel salt, and the soluble nickel salt is selected from at least one of nickel sulfate, nickel chloride or nickel nitrate; the cobalt source is selected from a soluble cobalt salt, and the soluble cobalt salt is selected from at least one of cobalt sulfate, cobalt chloride or cobalt nitrate; the manganese source is selected from a soluble manganese salt, and the soluble manganese salt is selected from at least one of manganese sulfate, manganese chloride or manganese nitrate; the salt containing the doping element M is selected from a soluble salt containing the doping element M, and the soluble salt containing the doping element M is, for example, a sulfate, a chloride or a nitrate; the precipitant is selected from sodium hydroxide and / or potassium hydroxide, and the complexing agent is selected from ammonia water.

[0089] In some embodiments, the base liquid is prepared under a protective gas atmosphere to avoid reaction during the base liquid preparation process (i.e., the base liquid is not prepared yet). The protective gas atmosphere is formed by introducing a protective gas into the reactor. The protective gas includes but is not limited to nitrogen, argon, helium, etc.

[0090] In some embodiments, the base solution is prepared at 40° C. to 70° C., which is consistent with the reaction temperature of the subsequent seed generation and growth stages, so as to facilitate the subsequent direct reaction.

[0091] In some embodiments, when preparing the base solution, the stirring speed is 400 rpm to 800 rpm.

[0092] In some embodiments, step S2 is performed in a first oxidizing atmosphere, and the flow ratio of oxygen to protective gas in the first oxidizing atmosphere is 1:0.2-5.0. In step S3, the seed crystal growth stage is performed in the first oxidizing atmosphere in the early stage, and the oxygen content is gradually reduced in the middle and late stages. If the oxygen content of the first oxidizing atmosphere is too high, it will cause the particles to grow too fast, the sphericity is poor, the particle size distribution is uneven, and the particle size distribution is uneven. (001) / I (101) becomes larger, and the proportion of (001) crystal plane is too high.

[0093] In some embodiments, in step S2, the flow ratio of the liquid A, liquid B and liquid C added to the base liquid at the same time is 100-200: 20-50: 1-4; exemplarily, when the effective volume of the reactor is 20L, the flow rate of the liquid A is 2L / h-4L / h, the flow rate of the liquid B is 400mL / h-1000mL / h, and the flow rate of the liquid C is 20mL / h-80mL / h. In step S3, the flow ratio of the liquid A, liquid B and liquid C added to the seed crystal at the same time is 100-200: 20-40: 1-4; exemplarily, when the effective volume of the reactor is 20L, the flow rate of the liquid A is 3L / h-6L / h, the flow rate of the liquid B is 600mL / h-1200mL / h, and the flow rate of the liquid C is 30mL / h-120mL / h. In the seed generation and growth stage, liquid A, liquid B and liquid C are introduced at the same time. By controlling the flow ratio of liquid A, liquid B and liquid C, the total flow rate of the material is controlled to control the reaction residence time, so as to avoid the particles growing fast, the sphericity is poor, and the nucleus is easy to explode due to too short residence time, or the particles growing slowly due to too long residence time. The total flow rate of the material is negatively correlated with the residence time, and the residence time can be calculated according to the following formula:

[0094]

[0095] Wherein, the total material flow rate is the sum of the flow rates of liquid A, liquid B and liquid C added simultaneously, and the effective volume of the reactor refers to the maximum liquid level that the agitator in the reactor can reach, that is, the position where the liquid level reaches the center line of the agitator blades. In actual operation, due to various factors (such as the stirring range of the agitator, the liquid level, etc.), the reactor cannot be completely filled. Therefore, the effective volume of the reactor is usually less than the reactor volume (i.e., the maximum chargeable volume). The reactor volume used in the following examples is 25L and the effective volume is 20L. The calculation method of the effective volume of the reactor is common knowledge and will not be repeated here.

[0096] In some embodiments, in step S2 and / or S3, the reaction temperature is 40°C to 70°C, which is the optimal range and is conducive to the normal growth of primary particles; if the reaction temperature is too low, it will cause insufficient growth dynamics and slow or stagnant particle size growth; if the reaction temperature is too high, it will cause the particles to grow too fast and the specific surface area will decrease.

[0097] In some embodiments, in step S2 and / or S3, the stirring speed is controlled at 300 rpm to 600 rpm. The stirring speed will affect the effective volume of the reactor, the reaction rate, and the physical and chemical properties of the precursor.

[0098] In some embodiments, the method for preparing the nickel-cobalt-manganese ternary precursor further includes: after obtaining particles that meet the target particle size requirements, stopping the reaction, collecting the reactor materials, performing solid-liquid separation, washing, drying, and sieving to obtain the nickel-cobalt-manganese ternary precursor. Among them, the target particle size is the particle size of the nickel-cobalt-manganese ternary precursor, for example, D50 is 9.0μm to 15.0μm. Exemplarily, when drying, the drying temperature is 100℃ to 120℃, the drying time is 8h to 12h, and the moisture content after drying is less than 0.5%. The above process is a conventional operation of the nickel-cobalt-manganese ternary precursor. Other process parameter requirements that are not limited or process details that are not recorded can be carried out in a conventional manner or in the prior art, and will not be described in detail here.

[0099] Another embodiment of the present invention provides a nickel-cobalt-manganese ternary material, which is prepared by sintering a precursor after mixing it with a lithium source, wherein the precursor includes the nickel-cobalt-manganese ternary precursor as described above and / or the nickel-cobalt-manganese ternary precursor prepared according to the method as described above. The nickel-cobalt-manganese ternary material prepared from the nickel-cobalt-manganese ternary precursor provided by the present invention can inherit most of the characteristics of the precursor, and its uniform and abundant internal pores provide more insertion and extraction channels for lithium ions, providing favorable conditions for the full infiltration of the electrolyte during the charge and discharge process, thereby obtaining a higher specific capacity; and with the insertion and extraction of lithium ions, the radial growth structure of the primary particles of the outer shell allows the stress generated by the ternary material during the charge and discharge process to be effectively released, slowing down the collapse of the material structure caused by anisotropy.

[0100] In some embodiments, the molar stoichiometric ratio of the precursor to the lithium source is 1:1.05-1.12.

[0101] In some embodiments, the sintering process is performed in an oxidizing atmosphere (such as air or oxygen), the sintering temperature is 700° C. to 900° C., and the sintering time is 2 h to 20 h.

[0102] In some embodiments, the method for preparing the nickel-cobalt-manganese ternary material further includes: cooling after sintering, crushing, screening, and demagnetizing to obtain the nickel-cobalt-manganese ternary material.

[0103] Another embodiment of the present invention provides a secondary battery, including a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes the nickel-cobalt-manganese ternary material as described above.

[0104] In some embodiments, the secondary battery may be, for example, a lithium ion battery, a sodium ion battery, a potassium ion battery, etc., but is not limited thereto.

[0105] In some embodiments, the secondary battery is a lithium-ion battery, including an electrolyte, a shell, and a bare cell disposed in the shell, wherein the bare cell includes a positive electrode sheet, a separator, and a negative electrode sheet.

[0106] In a specific embodiment, the preparation method of the secondary battery includes the following steps: stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence to ensure that a separator is provided between any positive electrode sheet and any negative electrode sheet, and obtaining a multilayer laminate body by winding, and loading it into a battery casing as a bare cell. Finally, injecting an electrolyte into the casing once or multiple times so that the bare cell is completely immersed in the electrolyte. In other words, the electrolyte is injected and fills the entire internal space of the battery, and the positive electrode sheet, the separator, and the negative electrode sheet are completely immersed in the electrolyte.

[0107] In a specific embodiment, the preparation method of the secondary battery comprises the following steps: adding electrolyte dropwise to both sides of the diaphragm, and assembling the positive electrode shell, positive electrode sheet, diaphragm, negative electrode sheet and negative electrode shell in sequence in a glove box into a button battery.

[0108] In some embodiments, the positive electrode sheet includes a positive current collector and a positive active material layer coated on at least one surface of the positive current collector. Among them, the positive current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. Among them, the thickness of the positive current collector is, for example, 8μm to 15μm, and the single-sided coating thickness of the positive active material layer is, for example, 20μm to 100μm. Further, in a specific embodiment, the positive current collector is, for example, aluminum foil, and the thickness of the aluminum foil is, for example, 13μμm, and the single-sided coating thickness of the positive active material layer is 50μm.

[0109] In some embodiments, the positive electrode active material layer includes a positive electrode active material, a binder, and a conductive agent, etc. The mass ratio of the positive electrode active material, the conductive agent, and the binder can be, for example, 90-98:1-5:1-5. Among them, the positive electrode active material can only use the high nickel single crystal positive electrode material as described above, and other materials commonly used as positive electrode active materials can also be added, such as Li x [Ni y Co z Mn t M (1-y-z-t) ]O 2-δmaterial, wherein M is selected from at least one of Cr, Zr, Ca, Mg, Cu, Ti, Al, Mo, W or Zn, 0.9<x<1.1, 0.65≤y<1.0, 0≤z<0.5, 0≤t<0.5, 0≤δ≤0.1, including but not limited to lithium nickel manganese oxide, lithium iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide. The binder is, for example, selected from any one or more of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene or styrene butadiene rubber (SBR). The conductive agent is, for example, selected from any one or more of conductive carbon black (SuperP), acetylene black, carbon nanotubes and graphene.

[0110] In a specific embodiment, the positive electrode active material is, for example, the high nickel single crystal positive electrode material as described above, the binder is, for example, selected from polyvinylidene fluoride, and the conductive agent is, for example, selected from conductive carbon black. After the positive electrode active material, the conductive agent and the binder are mixed, for example, in a mass ratio of 98:1:1, an organic solvent is added, and the system is stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry. Among them, the organic solvent is, for example, selected from N-methylpyrrolidone (NMP). The positive electrode slurry is evenly coated on an aluminum foil, and then transferred to an oven for drying after drying at room temperature, and the positive electrode sheet is obtained through cold pressing and slitting. In other embodiments, the positive electrode sheet can also be obtained by any other method of forming a positive electrode sheet.

[0111] In some embodiments, the negative electrode sheet in the above embodiments and / or examples includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. Among them, the negative electrode current collector is, for example, selected from any one of a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector or a stainless steel current collector, and the thickness of the negative electrode current collector is, for example, 8 μm to 15 μm, and the single-sided coating thickness of the negative electrode active material layer is, for example, 10 μm to 80 μm. In a specific embodiment, the negative electrode current collector is, for example, copper foil, and the thickness of the copper foil is, for example, 13 μm, and the single-sided coating thickness of the negative electrode active material layer is 50 μm.

[0112] In some embodiments, the negative electrode active material layer includes a negative electrode active material, a conductive agent, a binder, and a thickener, and the mass ratio of the negative electrode active material, the conductive agent, the binder, and the thickener can be, for example, 90 to 96: 1 to 2: 1 to 3: 2 to 5. The negative electrode active material is a compound capable of inserting and deinserting lithium ions, such as graphite, soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxide (SiO x , 0<x<2), at least one of silicon carbon compound or lithium titanate. The conductive agent is selected from any one or more of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes and graphene. The binder is selected from any one or more of polyvinylidene fluoride, polyethylene oxide, polyamide, polypropylene, polyacrylate, polyvinyl ether, polymethyl methacrylate, polyhexafluoropropylene or styrene-butadiene rubber. The thickener is selected from carboxymethyl cellulose sodium (CMC-Na) and the like.

[0113] In a specific embodiment, the negative electrode active material is selected from graphite, the conductive agent is selected from acetylene black, the binder is selected from styrene-butadiene rubber, and the thickener is selected from sodium carboxymethyl cellulose. The negative electrode active material, conductive agent, binder, and thickener are mixed in a mass ratio of 96:2:1:1, deionized water is added, and mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry, which is coated on a copper foil, and then transferred to an oven for drying after drying at room temperature, and then cold pressed and cut to obtain a negative electrode sheet. In other embodiments, the negative electrode sheet can also be obtained by any other method of forming a negative electrode sheet.

[0114] In some embodiments, the electrolyte includes electrolyte lithium salt, solvent and additive. In secondary batteries, the electrolyte plays the role of conducting ions, providing ion channels and maintaining chemical stability. The various components in the electrolyte can be divided into electrolyte lithium salt, solvent and additive according to their functions and dosages. Lithium salt is mainly used to provide lithium ions to form ion channels. In the entire electrochemical system of the battery, the directional movement of lithium ions and electrons generates electricity. Lithium salt has a great influence on the energy density, power density, wide electrochemical window, cycle life and safety performance of lithium batteries; solvent is used to dissolve lithium salt and additive; additive is a small amount of substance added to the electrolyte, there are many kinds and each plays a different role, for example, it can play a different improvement effect on the high and low temperature performance, cycle performance, film forming performance of the battery.

[0115] In some embodiments, the electrolyte lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(trifluoromethyl)sulfonyl imide, lithium bis(trifluoromethyl)sulfonyl imide, lithium acetate, lithium methane sulfonate, or lithium trifluoromethyl sulfonate, and the mass percentage of the electrolyte lithium salt is 12% to 16% based on the total mass of the electrolyte. The present invention does not limit the type of lithium salt, and a single lithium salt or a mixed lithium salt can be used.

[0116] In some embodiments, the solvent is selected from at least one of carbonate solvents, carboxylate solvents, ether solvents or nitrile solvents, and based on the total mass of the electrolyte, the mass percentage of the solvent is 70% to 80%. Among them, carbonate solvents are selected from ethylene carbonate, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, polycarbonate, etc., carboxylate solvents are selected from ethyl formate, ethyl acetate, propyl acetate, ethyl propionate, propyl propionate, etc., ether solvents are selected from ethylene glycol dimethyl ether, diethanol diethyl ether, etc., and nitrile solvents are selected from acetonitrile, propionitrile, butyronitrile, valeronitrile, etc. The present invention does not limit the type of solvent, and a single solvent or a mixed solvent can be used.

[0117] In some embodiments, the additive is selected from at least one of virtual console (VC), methylene methanedisulfonate (MMDS), propylene sulfite (PS), 1,3,2-dioxathiolane 2,2-dioxide (DTD) and ethylenesulfite (ES), and the mass percentage of the additive is 0.1% to 5% based on the total mass of the electrolyte. The present invention does not limit the type of additive, and a single additive or a mixed additive can be used.

[0118] In some embodiments, the membrane is, for example, a polyethylene (PE) film, a polypropylene (PP) film, a glass fiber film, or a composite film, and the thickness of the membrane is, for example, 9 μm to 15 μm.

[0119] The following specific examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to specifically illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range according to the description herein, and are not limited to the specific values ​​​​exemplified below.

[0120] According to the preparation process parameters in Table 1, the nickel-cobalt-manganese ternary precursors of Examples 1 to 10 and Comparative Examples 1 to 4 were prepared respectively according to the following method, and then sintered to obtain the nickel-cobalt-manganese ternary material. Finally, the nickel-cobalt-manganese ternary material was used as the positive electrode active material to make button batteries, the materials were characterized and the performance was tested, and the battery performance was tested. The test results are shown in Tables 2, 3 and 4.

[0121] 1. Preparation of nickel-cobalt-manganese ternary precursor, the steps are as follows:

[0122] 1.1. Nickel salt, cobalt salt and manganese salt were prepared into liquid A with a metal concentration of 2.0 mol / L according to a metal molar ratio of 0.94:0.02:0.04, 32 wt% NaOH solution was used as liquid B, and 20 wt% ammonia water was used as liquid C.

[0123] 1.2. Preparation of base liquid: nitrogen was introduced into the 25L first reaction kettle (effective volume was 20L) as protective gas, and base liquid was prepared by mixing liquid A, liquid B and liquid C. The pH value and ammonia value of the base liquid were controlled according to Table 1, the temperature was controlled at 50°C, and the stirring speed was controlled at 600rpm.

[0124] 1.3. Preparation of ternary precursor seed crystals: Liquid A, liquid B and liquid C are added into the reactor at a certain speed at the same time, the flow rate of liquid A is 4L / h, the flow rate of liquid B is 800ml / h, and the flow rate of liquid C is 40ml / h; at the same time, the volume proportions of oxygen and nitrogen in the reaction atmosphere are controlled according to Table 1, and the mixing reaction is carried out until the material reaches the full reactor, then the feeding is stopped, and the solid-liquid separation and washing are carried out to obtain the ternary precursor seed crystals.

[0125] 1.4. The ternary precursor was obtained by using the above seed growth: the seed was put into a 25L second reactor (different rotation speeds correspond to different effective volumes, and the stirring speed is in the range of 400rpm to 600rpm. The effective volumes are not much different, so the effective volumes are all calculated as 20L), and liquid A, liquid B and liquid C were added to the second reactor respectively. The flow rate of liquid A is 4L / h, the flow rate of liquid B is 800ml / h, and the flow rate of liquid C is 40ml / h. The pH value, ammonia value and stirring speed were controlled according to Table 1, and the temperature was controlled at 50°C. At the same time, the oxygen content of the reaction atmosphere was gradually reduced according to Table 1 or the reaction atmosphere was kept unchanged, and the machine was stopped when D50 reached the target particle size.

[0126] 1.5. The material in step 1.4 is subjected to solid-liquid separation, washing, drying and sieving to obtain a nickel-cobalt-manganese ternary precursor.

[0127] 2. Preparation of nickel-cobalt-manganese ternary materials, the steps are as follows:

[0128] 2.1. Mix the nickel-cobalt-manganese ternary precursor and lithium salt in a molar ratio of 1:1.05 by a high-speed mixer to obtain a mixed powder.

[0129] 2.2. The mixed powder is sintered at 800°C for 10 hours and then cooled. After coarse crushing, pulverizing, screening and demagnetization, a nickel-cobalt-manganese ternary material is obtained.

[0130] 3. The production steps of button batteries are as follows:

[0131] 3.1. Preparation of positive electrode sheets: Nickel-cobalt-manganese ternary material is used as the positive electrode active material, mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 92.5:5:2.5, NMP is added, and the mixture is fully stirred to prepare a positive electrode slurry; the positive electrode slurry is evenly coated on aluminum foil, placed in a forced air drying oven and dried at 120°C for 10 minutes, and finally the dried electrode sheet is rolled and cut to make a positive electrode sheet.

[0132] 3.2. Button cell assembly: Prepare an electrolyte with a LiPF6 concentration of 1.0 mol / L using ethylene carbonate and diethyl carbonate in a volume ratio of 1:1 as solvent and LiPF6 as lithium salt; use metal lithium foil as the negative electrode and Celgard 2400 polypropylene (PP) film as the separator, drip 35 μL of electrolyte on both sides of the separator, and assemble the button cell (CR 2025 type) of the positive electrode shell, positive electrode sheet, separator, negative electrode sheet and negative electrode shell in the glove box in sequence. Place at room temperature for 24 hours to allow the electrolyte to fully infiltrate the electrode before conducting subsequent battery tests.

[0133] 4. Material characterization and performance testing, battery performance testing

[0134] 4.1. Specific surface area test method of precursor:

[0135] The instrument used is Tristar II Surface Area and Porosity, manufactured by Micromeritics. The weighed powder is placed in a sample tube, the heating temperature is 120°C, and the test time is 2 hours. The adsorption amount of the adsorbate molecule (N2) of the sample is determined based on the pressure or weight change before and after adsorption, thereby obtaining the specific surface area.

[0136] 4.2. Test method for tap density of precursor:

[0137] The instrument used is AUTOTAP tapped density analyzer, manufactured by Quantachrome. The weighed powder is loaded into the measuring cylinder of the vibrating device, and the measuring cylinder is fixed on the support. The cam is turned, and the directional rod drives the support to slide up and down and hit the anvil. Vibrate 250±15 times per minute for 12 minutes to compress the gaps between the particles as much as possible. When the volume of the powder no longer decreases, read the volume of the powder in the measuring cylinder. The ratio of the powder mass to the volume is the tap density of the powder.

[0138] 4.3. Precursor roundness test method:

[0139] Take a scanning electron microscope (SEM) image of the material and select an image with relatively dispersed particles. Use Shimadzu image processing software to calculate the projected area S and projected perimeter P of the particles. The roundness Q is calculated according to the following formula:

[0140]

[0141] 4.4、Test methods for other indicators of precursors:

[0142] The material was characterized by SEM and X-ray Diffraction (XRD). The peak intensity ratio I(001) / I(101) was determined based on the XRD pattern. The SEM images and SEM cross-section (CP) images taken at the same magnification were measured using particle size testing software. Each sample was measured multiple times and the average value was taken to obtain the secondary particle size of the precursor, the length and width of the primary particles, the core radius and the shell thickness.

[0143] Figure 1 , Figure 2 and Figure 3 The XRD pattern, SEM pattern and SEM cross-sectional (CP) pattern of the nickel-cobalt-manganese ternary precursor prepared in Example 1 are shown in sequence.

[0144] from Figure 2 and 3It can be seen that the secondary particle structure of the nickel-cobalt-manganese ternary precursor prepared in Example 1 is spherical, and the primary particles are spindle-shaped.

[0145] Please refer to Figure 2 , where the length of line 2 represents the length of the primary particle, and the length of line 3 represents the width of the primary particle. The length and width of the primary particle are measured and the ratio of the two is calculated to obtain the aspect ratio.

[0146] Please refer to Figure 3 The core / shell porosity was obtained by calculating the ratio of the longitudinal cross-sectional area of ​​all pores in the core / shell on the SEM (or TEM) image to the longitudinal cross-sectional area of ​​the core / shell using Image-pro plus software.

[0147] 4.5. Test method for button cell performance:

[0148] In a constant temperature box at 25°C, charge and discharge tests were carried out at a current of 0.33C in the voltage range of 2.8V to 425V, and the cycle performance test at a rate of 1C was carried out at a current of 0.33C in the voltage range of 2.8V to 425V.

[0149] Table 1 Precursor preparation process parameters

[0150]

[0151] Note: In Table 1, "V(O2):V(N2)" refers to the volume ratio of oxygen and nitrogen in the reaction atmosphere; "1:0.5→1:1→1:2" means that when D50 reaches 5.0μm, the volume ratio of oxygen and nitrogen in the reaction atmosphere decreases from 1:0.5 to 1:1, and when D50 reaches 8.0μm, the volume ratio of oxygen and nitrogen in the reaction atmosphere decreases from 1:1 to 1:2, and other similar expressions also have the same meaning; "V(O2):V(N2)=0:1" refers to pure nitrogen, and "V(O2:V(N2) is always 0:1" means that the nitrogen atmosphere is always maintained; "V(O2):V(N2)=1:0" refers to pure oxygen, "V(O2:V(N2) is always 1:1", and "V(O2:V(N2) is always 1:5" means that the oxygen content of the oxidizing atmosphere remains unchanged.

[0152] Table 2 Precursor characteristics (I)

[0153]

[0154]

[0155] Table 3 Precursor characteristics (II)

[0156]

[0157] Table 4 Button battery test results

[0158] Charging capacity (mAh / g) Discharge capacity (mAh / g) First effect ICE (%) 100 cycles capacity retention rate (%) Example 1 251.8 219.6 87.2 93.5 Example 2 250.0 216.9 86.8 90.1 Example 3 247.8 215.4 86.9 88.7 Example 4 249.1 214.5 86.1 92.8 Example 5 246.7 214.7 87.0 89.7 Example 6 247.4 214.4 86.7 90.4 Example 7 251.2 218.0 86.8 91.5 Example 8 249.3 217.1 87.1 92.4 Example 9 250.1 216.8 86.7 90.5 Example 10 245.6 213.8 87.1 92.1 Comparative Example 1 249.5 215.6 86.4 90.5 Comparative Example 2 247.6 213.6 86.3 89.7 Comparative Example 3 249.2 214.9 86.2 88.5 Comparative Example 4 247.3 213.2 86.2 85.2

[0159] From the data in Tables 1 to 4, we can draw the following conclusions:

[0160] The battery specific capacity and cycle performance of Example 1 are better than those of Comparative Examples 1 to 4. The reason may be that the large-particle nickel-cobalt-manganese ternary precursor inherits most of the characteristics of the precursor in the process of preparing the nickel-cobalt-manganese ternary material. The uniform and abundant pores inside it provide more intercalation and deintercalation channels for lithium ions, which provides favorable conditions for the sufficient infiltration of the electrolyte during the charge and discharge process, thereby obtaining a higher specific capacity; and with the intercalation and deintercalation of lithium ions, the radial growth structure of the primary particles in the outer shell allows the stress generated by the ternary material during the charge and discharge process to be effectively released, thereby slowing down the collapse of the material structure caused by anisotropy.

[0161] Compared with Example 1, the base liquid pH and ammonia value of Comparative Example 1 are too low, and the base liquid pH is not much different from the crystal growth pH, ​​the base liquid ammonia value is the same as the crystal growth ammonia value, the obtained precursor tap density is too low, the roundness Q is 83%, the sphericity is poor, I(001) / I(101) is too large, the span is too large, the particle size distribution is uneven, and the shell porosity is too large.

[0162] Compared with Example 1, the bottom liquid ammonia value of Comparative Example 2 is too low, the oxygen content in the crystal formation and growth stages is too high, the resulting precursor I(001) / I(101) is too large, the span is too large, the particle size distribution is uneven, and the porosity of the inner core and the outer shell is too large.

[0163] Compared with Example 1, the bottom liquid ammonia value of Comparative Example 3 is too low, the crystal formation and growth stages are always carried out in a pure nitrogen atmosphere, the tap density of the obtained precursor is too low, I(001) / I(101) is too large, the Span is too large, the particle size distribution is uneven, the shell porosity is too small, and the length and width of the primary particles are too large.

[0164] Compared with Example 1, the bottom liquid ammonia value of Comparative Example 4 is too low, the crystal formation stage is carried out under a pure oxygen atmosphere, the oxygen content in the crystal growth stage is too high, the tap density of the obtained precursor is too low, I(001) / I(101) is too large, the Span is too large, and the particle size distribution is uneven.

[0165] Among them, if the span of the precursor is too large, the particles with smaller particle size will be overburned during the sintering process, which will lead to poor performance of the specific capacity of the positive electrode material. The precursor with poor sphericity has a relatively longer ion migration path after sintering, which will also lead to poor performance of the specific capacity of the positive electrode material. If the tap density of the precursor is too low, it will be inherited into the positive electrode material, resulting in poor performance of the specific capacity of the positive electrode material; at the same time, if the tap density of the precursor is too low, the BET will be too large, which will be beneficial to the performance of the capacity of the positive electrode material to a certain extent, but it will also cause large gas production and poor cycle performance.

[0166] It should be noted that in the present invention, based on the inventive concept, the nickel-cobalt-manganese ternary precursor provided by the present invention can be doped with other elements M, and the chemical formula is (Ni x Co y Mn z M a )(OH)2, wherein 0.9<x≤0.98, y>0, z>0, x+y+z=1, 0≤a≤0.01, further, the M element can be selected from Al, Mg, Zr, Ti, Cu, Zn, etc., with a content of 3000-8000ppm, which does not affect the purpose of the present invention and is within the protection scope of the present invention.

[0167] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A nickel-cobalt-manganese ternary precursor, characterized in that: The chemical formula of the nickel-cobalt-manganese ternary precursor is (Ni x Co y Mn z M a )(OH)2, wherein 0.9<x≤0.98, y>0, z>0, x+y+z=1, 0≤a≤0.01, M is a doping element; The nickel-cobalt-manganese ternary precursor is a secondary particle composed of primary particles, including a core and a shell; The tap density TD of the secondary particles is 2.0 g / cm 3 <TD<2.2g / cm 3 , the specific surface area BET is 10m 2 / g<BET<20m 2 / g.

2. The nickel-cobalt-manganese ternary precursor according to claim 1, characterized in that: The nickel-cobalt-manganese ternary precursor satisfies at least one of the following performance parameters (A1) to (A6): (A1), the inner core has pores, and the porosity is 5% to 10%; (A2), the shell has pores, and the porosity is 1% to 5%; (A3) The shell is composed of primary particles, and the primary particles growing radially toward the center of the shell account for more than 80%; (A4), more than 90% of the primary particles in the shell have an aspect ratio of 5.0 to 15.0; (A5), M is selected from at least one of Al, Mg, Zr, Ti, Cu and Zn; (A6) The mass content of M is 3000ppm to 8000ppm.

3. The nickel-cobalt-manganese ternary precursor according to claim 1, characterized in that: The nickel-cobalt-manganese ternary precursor satisfies at least one of the following performance parameters (A7) to (A13): (A7), 0.32<Span<0.45, Span is the particle size distribution width of the secondary particles; (A8), 1.0<I (001) / I (101) <1.5,I (001) / I (101) is the peak intensity ratio of the (001) peak to the (101) peak in the X-ray diffraction pattern; (A9) The secondary particle structure is spherical or quasi-spherical, and 90%<Q<100%, where Q is the roundness; (A10), secondary particle size D50 is 9.0 μm to 15.0 μm; (A11), the distance from the center of the inner core to the outer wall of the inner core is 5 to 9 μm; (A12), the thickness of the shell is 4 μm to 6 μm; (A13) The longitudinal cross-sectional area of ​​the shell accounts for 30% to 50% of the longitudinal cross-sectional area of ​​the secondary particle.

4. The nickel-cobalt-manganese ternary precursor according to any one of claims 1 to 3, characterized in that: The primary particles in the shell meet at least one of the following performance parameters (B1) to (B4): (B1), the primary particles are spindle-shaped; (B2), the length of the primary particles is 200nm to 700nm; (B3), the width of the primary particle is 40nm to 90nm; (B4) The angle between the length direction of the primary particle and the centripetal force direction is less than or equal to 30°.

5. A method for preparing a nickel-cobalt-manganese ternary precursor according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Prepare a base solution, wherein the pH of the base solution is 11 to 13 and the base solution contains 5 g / L to 8 g / L of a complexing agent; S2, adding liquid A, liquid B and liquid C to the base liquid at the same time to prepare seed crystals; S3, adding liquid A, liquid B and liquid C to the seed crystal at the same time, controlling the pH of the reaction system to 10-12, the concentration of the complexing agent in the reaction system to 3 g / L-6 g / L, and preparing the nickel-cobalt-manganese ternary precursor under a second oxidizing atmosphere; The A solution includes a nickel source, a cobalt source and a manganese source, the B solution includes a precipitant, and the C solution includes a complexing agent; The volume ratio of oxygen to protective gas in the second oxidizing atmosphere is 1:0.2-10, and the oxygen content in the second oxidizing atmosphere gradually decreases as the particle size increases until particles meeting the target particle size requirements are obtained.

6. The method for preparing the nickel-cobalt-manganese ternary precursor according to claim 5, characterized in that: The oxygen content in the second oxidizing atmosphere gradually decreases as the particle size increases until particles meeting the target particle size requirements are obtained, including: When the seed crystal grows to a particle size that reaches a first preset particle size requirement, the volume ratio of oxygen to protective gas in the second oxidizing atmosphere is 1:0.5-5.0; When the particle size reaches the second preset particle size requirement, the volume ratio of oxygen to protective gas in the second oxidizing atmosphere is 1:2-10; The first preset particle size requirement is smaller than the second preset particle size requirement.

7. The method for preparing the nickel-cobalt-manganese ternary precursor according to claim 5, characterized in that: In the liquid A, the molar ratio of nickel ions, cobalt ions and manganese ions is 0.9-0.98: 0.01-0.05: 0.01-0.05; And / or, the liquid A further comprises a salt containing a doping element M; And / or, the metal ion concentration in the liquid A is 1.5 mol / L to 2.5 mol / L; And / or, the liquid B comprises a precipitant having a mass concentration of 25wt% to 32wt%; And / or, the liquid C comprises a complexing agent at a mass concentration of 12wt% to 20wt%; and / or, the base liquid is prepared under a protective gas atmosphere; And / or, the base liquid is prepared at 40°C to 70°C; And / or, when preparing the base liquid, the stirring speed is 400 rpm to 800 rpm.

8. The method for preparing a nickel-cobalt-manganese ternary precursor according to any one of claims 5 to 7, characterized in that: The process is performed according to at least one of the following process conditions (C1) to (C4): (C1), step S2 is performed in a first oxidizing atmosphere, wherein the flow ratio of oxygen to protective gas in the first oxidizing atmosphere is 1:0.2-5.0; (C2), in step S2, the flow ratio of the liquid A, liquid B and liquid C added simultaneously to the base liquid is 100-200:20-50:1-4; (C3), in step S2 and / or S3, the reaction temperature is 40°C to 70°C; (C4), in step S2 and / or S3, the stirring speed is controlled at 300 rpm to 600 rpm; (C5) In step S3, the flow ratio of the A solution, the B solution and the C solution added simultaneously to the seed crystal is 100-200:20-40:1-4.

9. A nickel-cobalt-manganese ternary material, characterized in that: The precursor is prepared by mixing a precursor with a lithium source and then sintering the mixture, wherein the precursor includes the nickel-cobalt-manganese ternary precursor according to any one of claims 1 to 4 and / or the nickel-cobalt-manganese ternary precursor prepared according to the method according to any one of claims 5 to 8.

10. A secondary battery, characterized in that: It comprises a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises the nickel-cobalt-manganese ternary material according to claim 9.